Pharmacological Activation of cGAS for Cancer Immunotherapy - Garland, Kyle M.; Rosch, Jonah C.; Carson, Carcia S.; Wang-Bishop, Lihong; Hanna, Ann; Sevimli, Sema; Van Kaer, Casey; Balko, Justin M.; Ascano, Manuel; Wilson, John T. (Frontiers in Immunology, 2021)
When compartmentally mislocalized within cells, nucleic acids can be exceptionally immunostimulatory and can even trigger the immune-mediated elimination of cancer. Specifically, the accumulation of double-stranded DNA in the cytosol can efficiently promote antitumor immunity by activating the cGAMP synthase (cGAS) / stimulator of interferon genes (STING) cellular signaling pathway. Targeting this cytosolic DNA sensing pathway with interferon stimulatory DNA (ISD) is therefore an attractive immunotherapeutic strategy for the treatment of cancer. However, the therapeutic activity of ISD is limited by several drug delivery barriers, including susceptibility to deoxyribonuclease degradation, poor cellular uptake, and inefficient cytosolic delivery. Here, we describe the development of a nucleic acid immunotherapeutic, NanoISD, which overcomes critical delivery barriers that limit the activity of ISD and thereby promotes antitumor immunity through the pharmacological activation of cGAS at the forefront of the STING pathway. NanoISD is a nanoparticle formulation that has been engineered to confer deoxyribonuclease resistance, enhance cellular uptake, and promote endosomal escape of ISD into the cytosol, resulting in potent activation of the STING pathway via cGAS. NanoISD mediates the local production of proinflammatory cytokines via STING signaling. Accordingly, the intratumoral administration of NanoISD induces the infiltration of natural killer cells and T lymphocytes into murine tumors. The therapeutic efficacy of NanoISD is demonstrated in preclinical tumor models by attenuated tumor growth, prolonged survival, and an improved response to immune checkpoint blockade therapy.